The Effectiveness of Electronic Whiteboards on Students’ Reading Skills - Wahid, Jusmin HJ; Irawan, Iwan Irawan; Tidore, Sumiyati Tidore (JOLLT Journal of Languages and Language Teaching, 2021)
Technology has become a demand for students to master their reading skills. Technology right now plays an important role in the teaching and learning process. The lecturer are needed technology to improve their material and make their teaching are effective. It was expected that to apply the electronic whiteboard itself can use by the lecturer to design better ways for the students to acquire important information. It is realized that the fourth-semester students at the English Department of Khairun University are needed as much information on the electronic whiteboard as possible to improve their reading skills. This research is an experimental research that was held at the English Program at Khairun University Ternate. The experimental research involves two groups of students, they are the experimental group and the control group. The researcher used the English Program’s fourth-semester students at Khairun University Ternate as a research sample. The result of the t-test in the experimental class shows that the mean score of the pre-test was 74.90 and the means score of the post-test was 81.90. It shows that electronic whiteboards in the experimental class experienced significant improvement in students reading skills. Then, the standard deviation in the post-test was 5.58 and the standard deviation in the pre-test was 4.38. It could be concluded that the students get significant progress in their reading skills after applying the electronic whiteboard.